Phytochemical Composition and Antimicrobial Activity of Raphanus sativus, Brassica rapa, and Allium cepa: A Review Article - Mustafa J. Jalal,; Raghda W Khalid,; Hajir Dawood Sulaiman Joban, (American Journal of Biology and Natural Sciences, 2026)
It has been known that medicinal and dietary plants are a rich source of bioactive compounds possessing therapeutic potential. There are three vegetables that take a centre stage in the list of commonly consumed vegetables: Raphanus sativus (radish), Brassica rapa (turnip, Chinese cabbage, pak choi) and Allium cepa (onion), which are rich in phytochemicals and have been reported to be antimicrobial in nature. This review is a critical analysis of the phytochemical composition of the three species of plants and appraisal of available literatures on the antimicrobial activity of these plants against bacterial and fungal pathogens. There is a focus on the key types of secondary metabolites, antimicrobial action mechanisms, and the factors that affect bioactivity. This paper has identified the prospective of these vegetables as sources of natural antimicrobial agents by refining and synthesizing available research with in-text citations and identifying gaps in the future.